2020
DOI: 10.1111/nmo.14008
|View full text |Cite
|
Sign up to set email alerts
|

The added value of symptom analysis during a rapid drink challenge in high‐resolution esophageal manometry

Abstract: Over the past 20 years, high-resolution manometry (HRM) has become the gold standard for the diagnosis of esophageal motility disorders. The current HRM-based Chicago classification v3.0 (CC 3.0) 1 makes a distinction between major (achalasia, EGJ outflow obstruction, esophageal spasms, Jackhammer esophagus, and absent contractility) and minor motility disorders (ineffective esophageal motility) of uncertain clinical signification since they can be observed in a significant proportion of healthy subjects and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Additionally, the occurrence of typical symptoms during RDC in patients referred for investigation of dysphagia or other esophageal symptoms confirms the clinical relevance of any motility disorder identified during testing 29 . Clinical studies have shown that RDC can help to establish a conclusive diagnosis in patients with borderline HRM findings during single water swallows 26‐31 . Furthermore, up to 17% of patients with esophageal symptoms but normal wet swallows have abnormal RDC findings that require further investigation by addition of solid swallows to the HRM protocol and /or other diagnostic tests 31 …”
Section: Methodsmentioning
confidence: 52%
See 2 more Smart Citations
“…Additionally, the occurrence of typical symptoms during RDC in patients referred for investigation of dysphagia or other esophageal symptoms confirms the clinical relevance of any motility disorder identified during testing 29 . Clinical studies have shown that RDC can help to establish a conclusive diagnosis in patients with borderline HRM findings during single water swallows 26‐31 . Furthermore, up to 17% of patients with esophageal symptoms but normal wet swallows have abnormal RDC findings that require further investigation by addition of solid swallows to the HRM protocol and /or other diagnostic tests 31 …”
Section: Methodsmentioning
confidence: 52%
“…Characteristic findings during RDC include a normal (“hypopressive”) pattern shared by healthy subjects and patients with IEM, that discriminates patients with non‐obstructive hypercontractile motility or achalasia (sensitivity 80% and specificity 93%), (ii) impaired deglutitive inhibition (“brief hyperpressive” pattern) in patients with non‐obstructive hypercontractile disorders (eg, distal spasm, hypercontractile esophagus), and (iii) impaired EGJ function (“prolonged hyperpressive” pattern) with increased RDC‐IRP that discriminates achalasia and EGJOO from other patients groups (sensitivity 70% and specificity 85%) 28 . Additionally, the occurrence of typical symptoms during RDC in patients referred for investigation of dysphagia or other esophageal symptoms confirms the clinical relevance of any motility disorder identified during testing 29 . Clinical studies have shown that RDC can help to establish a conclusive diagnosis in patients with borderline HRM findings during single water swallows 26‐31 .…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…Administration of a standardized meal during HRM can also demonstrate latent obstruction and augmentation of esophageal body contraction, although the test is limited because it is cumbersome, time‐consuming, and the meal administered may not be similar across motility centers. Symptom analysis during provocative tests (both RDC and STM) may have adjunctive value in the evaluation of symptomatic patients, but recording and grading of symptoms have not been standardized to date 15,28 …”
Section: Provocative Testingmentioning
confidence: 99%
“…ously,16 but sometimes the test is difficult to interpret due to various symptoms (cough, nausea) occurring in up to 10% of patients with normal or minor motility disorders 25. Further studies are required to determine whether SFS can be useful to confirm an EGJ obstruction (or identify other major esophageal motility disorders) in patients with normal or minor motility with SWS but pressurization during RDC.…”
mentioning
confidence: 99%